The reef [videorecording (DVD)] - Walshe-Howling, Damian, 1971-; Naylor, Zoe, 1977-; Pickering, Adrienne, 1981-; Traucki, Andrew (Image Entertainment, 2011)
On the beautiful but dangerous waters of Australia's Great Barrier Reef, ship delivery man Luke and four friends chart a yacht to its new owner. Along the way, their ship is torn open by sharp rocks and begins to sink, leaving the passengers with a terrifying choice: stay on board with slim hope of rescue, or swim twelve miles to the nearest island, through shark-infested waters.